2013
DOI: 10.3348/kjr.2013.14.3.446
|View full text |Cite
|
Sign up to set email alerts
|

Modified Retroperitoneal Access for Percutaneous Intervention after Pancreaticoduodenectomy

Abstract: Percutaneous access to the surgical bed after pancreaticoduodenectomy can be a challenge, due to the post-operative anatomy alteration. However, immediate complications, such as surgical bed abscess or suspected tumor recurrence, are often best accessed percutaneously, as open surgical or endoscopic approaches are often difficult, if not impossible. We, hereby, describe a safe approach that is highly replicable, in accessing the surgical bed for percutaneous intervention, following pancreaticoduodenectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…18). Following PD, a collection in the deep surgical bed surrounding the pancreatic-intestinal anastomosis can be accessed through the right anterior pararenal fascia using hydrodissection for displacement of the colon [68]. Subphrenic collections are common in both the post-operative setting and pancreatitis and preferably drained via a subcostal approach to avoid pleural transgression and associated risks of fistula and empyema.…”
Section: Access Routesmentioning
confidence: 99%
“…18). Following PD, a collection in the deep surgical bed surrounding the pancreatic-intestinal anastomosis can be accessed through the right anterior pararenal fascia using hydrodissection for displacement of the colon [68]. Subphrenic collections are common in both the post-operative setting and pancreatitis and preferably drained via a subcostal approach to avoid pleural transgression and associated risks of fistula and empyema.…”
Section: Access Routesmentioning
confidence: 99%
“…We read the article titled 'Modified Retroperitoneal Access for Percutaneous Intervention after Pancreaticoduodenectomy' by Uei Pua et al ( 1 ) published in Korean J Radiol (2013;14:446-450) with a great interest. Therein, authors reported two cases which needed retroperitoneal access.…”
mentioning
confidence: 99%